The Cattle Fever Tick, Rhipicephalus microplus, as a Model for Forward Pharmacology to Elucidate Kinin GPCR Function in the Acari - Xiong, Caixing; Baker, Dwight; Pietrantonio, Patricia V. (Frontiers in Physiology, 2019)
The success of the acaricide amitraz, a ligand of the tick tyramine/octopamine receptor (a G protein-coupled receptor; GPCR), stimulated interest on arthropod-specific GPCRs as targets to control tick populations. This search advances tick physiology because little is known about the pharmacology of tick GPCRs, their endogenous ligands or their physiological functions. Here we explored the tick kinin receptor, a neuropeptide GPCR, and its ligands. Kinins are pleiotropic insect neuropeptides but their function in ticks is unknown. The endogenous tick kinins are unknown and their cDNAs have not been cloned in any species. In contrast, more than 271 insect kinin sequences are available in the DINeR database. To fill this gap, we cloned the kinin cDNA from the cattle fever tick, Rhipicephalus microplus, which encodes 17 predicted kinins, and verified the kinin gene structure. We predicted the kinin precursor sequences from additional seven tick species, including Ixodes scapularis. All species showed an expansion of kinin paracopies. The “kinin core” (minimal active sequence) of tick kinins FX1X2WGamide is similar to those in insects. Pro was predominant at the X2 position in tick kinins. Towards accelerating the discovery of kinin function in ticks we searched for novel synthetic receptor ligands. We developed a dual-injection assay for functional screens of small molecules and/or peptidomimetics that uses a fluorescent calcium reporter. A commercial library of fourteen small molecules antagonists of mammalian neurokinin (NK) receptors was screened using this endpoint assay. One acted as full antagonist (TKSM02) with inhibitory concentration fifty (IC50) of 45 µM, and three were partial antagonists. A subsequent calcium bioluminescence assay tested these 4 antagonists through kinetic curves and confirmed TKSM02 as full antagonist and one as partial antagonist (TKSM14). Antagonists of NK receptors displayed selectivity (>10,000-fold) on the tick kinin receptor. Three peptidomimetic ligands of the mammalian NK receptors (hemokinin 1, antagonist G and spantide I) were tested in the bioluminescence assay but none were active. Forward approaches may accelerate discovery of kinin ligands, either as reagents for tick physiological research or as lead molecules for acaricide development, and they demonstrate that selectivity is achievable between mammalian and tick neuropeptide systems.